TRANSFORMASI PEMBELAJARAN KEBUGARAN JASMANI DAMPAK PROJECT BASED LEARNING TERHADAP MOTIVASI PESERTA DIDIK - Dopong, Maulana Malik; Priambodo, Anung; Wibowo, Sapto; Ridwan, Mochamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the impact of the Project-Based Learning (PjBL) model on students’ learning motivation in the context of physical fitness education. Employing a pre-experimental approach with a one-group pretest-posttest design, the study involved 23 fifth-grade elementary students, selected using purposive sampling based on specific criteria. A learning motivation questionnaire was utilized as the main instrument, and the data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the paired sample t-test. Results showed an increase in the average motivation score from 23.35 (pretest) to 25.65 (posttest). The data met the assumption of normality, with a significance value above 0.05. The paired sample t-test revealed a significance level of 0.000, indicating a statistically significant difference before and after the implementation of the PjBL model. In conclusion, Project-Based Learning has a significant positive effect on improving students’ motivation, offering a more engaging, contextual, and meaningful learning experience.